Nilai Ganbaru dalam Manga Hajime No Ippo Karya Morikawa Joji - Marina Ambari, Ni Putu (Humanis, 2017)
This research entitled "Ganbaru Value In Hajime No Ippo Comics Written by Morikawa Joji". This research aims to determine the factors that affect ganbaru value shown by figures Makunouchi Ippo and various kinds of ganbaru values that illustrated in Hajime No Ippo comics. Theories that used for analyzing are the theory of sociology of literature proposed by Wellek and Warren (1990), learning motivation by Slameto (1995) as well as Dimyati with Mudjiono (1999), and semiotics by Danesi (2010). Results of this research showed that there are two main factors forming ganbaru value shown by the character Makunouchi Ippo with  total of eight sub forming factors and there are eight ganbaru values that reflected in Hajime No Ippo comics.